2003
DOI: 10.4028/www.scientific.net/msf.433-436.953
|View full text |Cite
|
Sign up to set email alerts
|

MISiCFET Chemical Sensors for Applications in Exhaust Gases and Flue Gases

Abstract: A chemical gas sensor based on a silicon carbide field effect transistor with a catalytic gate metal has been under development for a number of years. The choice of silicon carbide as the semiconductor material allows the sensor to operate at high temperatures, for more than 6 months in flue gases at 300°C and for at least three days at 700°C. The chemical inertness of silicon carbide and a buried gate design makes it a suitable sensor technology for applications in corrosive environments such as exhaust gases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Whilst large boiler and commercial premises assess their pollution using Fourier transform infrared (FTIR) spectroscopy, the cost of these systems is too high for small installations, such as domestic central heating boilers. It has been shown that silicon carbide sensors can be used to determine the mode of operation for a boiler operating on wood pellets [49]. This showed that the CO concentration in the exhaust varies between 80 and 500 ppm, with an NO variation between 60 and 100 ppm, which correlated well with the measured oxygen concentration.…”
Section: Combustion Controlmentioning
confidence: 73%
See 1 more Smart Citation
“…Whilst large boiler and commercial premises assess their pollution using Fourier transform infrared (FTIR) spectroscopy, the cost of these systems is too high for small installations, such as domestic central heating boilers. It has been shown that silicon carbide sensors can be used to determine the mode of operation for a boiler operating on wood pellets [49]. This showed that the CO concentration in the exhaust varies between 80 and 500 ppm, with an NO variation between 60 and 100 ppm, which correlated well with the measured oxygen concentration.…”
Section: Combustion Controlmentioning
confidence: 73%
“…The sensitivity of the catalytic sensor to a gas is determined by both the choice of the metal and the temperature of operation [48]. For example, comparisons between the ammonia senisitivity of sensors with Pt and Ir gates over the temperature range 150-400 • C have shown that, although both metallizations give a maximum sensor signal of 1200 mV, the Ir device has a maximum sensitivity at 300 • C and the Pt device at 225 • C [49]. The temperature dependence is further complicated when the operational temperature exceeds 600 • C, where the sensors begin to operate in a binary fashion, where the reaction rate at the metal surface increases dramatically [50].…”
Section: Gas Sensorsmentioning
confidence: 99%
“…., 7) located along the longitudinal axis of the aluminum block (see figure 5). The inaccuracy of measurements was f 2 "C. The block mounting laboratory set-up was also used in the study of sensitivity, selectivity and response time of the sensors from the chemical viewpoint, which is beyond the content of this paper [6].…”
Section: Flotherm Modelmentioning
confidence: 99%
“…No special simulation-based study of the heat sink efficiency in terms of fin spacing in natural convection conditions was performed. However, approximate evaluation of the optimum fin spacing for the tins aligned with gravity was made according to the calculation technique reported in [7]. The obtained fin spacing was close to 6 mm, which was used in tube mounting design:;.…”
Section: Measured T Calculatedmentioning
confidence: 99%